2014
DOI: 10.3324/haematol.2014.114934
|View full text |Cite
|
Sign up to set email alerts
|

Absolute peripheral monocyte count at diagnosis predicts central nervous system relapse in diffuse large B-cell lymphoma

Abstract: ABSTRACTnation of blood smears in cases in which the automated counts were abnormal.CNS relapse-free survival was calculated by cause-specific function, censoring patients who died without CNS relapse, in accordance with previously published studies.11-14 The starting date of the time-to-event analysis was defined at diagnosis. Univariate and multivariate analyses of estimated risk factors for CNS relapse in DLBCL patients were performed using the log-rank test and Cox proportional hazard regression analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…A recent study has also reported that high AMC predicates decreased cancer‐specific survival in patients with ESCC on univariate analysis . Our results were similar with previous findings that high monocyte count at diagnosis has been shown to be a significant risk factor for systemic relapse and central nervous system relapse in diffuse large B‐cell lymphoma . Kumagai et al .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A recent study has also reported that high AMC predicates decreased cancer‐specific survival in patients with ESCC on univariate analysis . Our results were similar with previous findings that high monocyte count at diagnosis has been shown to be a significant risk factor for systemic relapse and central nervous system relapse in diffuse large B‐cell lymphoma . Kumagai et al .…”
Section: Discussionsupporting
confidence: 93%
“…24 Our results were similar with previous findings that high monocyte count at diagnosis has been shown to be a significant risk factor for systemic relapse and central nervous system relapse in diffuse large B-cell lymphoma. 25,26 Kumagai et al analyzed data from 302 consecutive patients with lung adenocarcinoma who received curative resection, and found that elevated AMC was associated with poorer recurrence-free survival and overall sur-vival. 17 Subimerb et al also reported that a higher frequency of patients surviving 11 months was found in cholangiocarcinoma patients with low levels of monocytes than those with high levels of monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that disparities may be eliminated or minimized by dose optimization . A high absolute monocyte count has also been previously identified as an adverse prognostic factor for survival in patients with large cell lymphoma, although there are differences in optimal cutoff values in clinical trials . A high monocyte count may be associated with the suppression of host antitumor immunity and the promotion of tumor angiogenesis, and this results in aggressive clinical behavior in patients with DLBCL .…”
Section: Discussionmentioning
confidence: 99%
“…27 A high absolute monocyte count has also been previously identified as an adverse prognostic factor for survival in patients with large cell lymphoma, although there are differences in optimal cutoff values in clinical trials. [28][29][30] A high monocyte count may be associated with the suppression of host antitumor immunity and the promotion of tumor angiogenesis, and this results in aggressive clinical behavior in patients with DLBCL. 30,31 Finally, higher CCI scores are associated with higher rates of TRM and subsequently shorter OS, particularly in patients with a CCI score 5.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphopenia, a surrogate marker of immune suppression, was found to predict survival in diffuse large B cell lymphoma (DLBCL) [16] and extranodal NK/T cell lymphoma (ENKTL) [22]. Monocytes, which are considered immunologically relevant and regarded as a surrogate marker of the tumor microenvironment, were also recently reported to be a prognostic factor in DLBCL [23,24], ENKTL [25], and Hodgkin's lymphoma (HL) [26]. In this study, we performed a large retrospective cohort study on adult patients with sporadic BL and investigated the prognostic value of pretreatment lymphocyte to monocyte ratio (LMR).…”
Section: Introductionmentioning
confidence: 98%